Looking Back to Look Forward: After Forty Years of Alma Ata Declaration, What are Our Priorities? - Srinivas, Sunitha (Indian Journal of Pharmacy Practice)
Public health history is marked by several momentous events, and 12th September 1978, was one of those. Delegation from 134 countries, 67 international organisations, and many non-governmental organisations joined the World Health Organisation and UNICEF at the International Conference on Primary Health Care at Alma-Ata, Kazakhstan, USSR from 6th to 12th Sep 1978 and this culminated in the Declaration of Alma Ata.1 The zealous goal of ‘Health for All by 2000’ based on primary health care (PHC) was the driving force of this Declaration. Amongst various aspects, the Declaration stated that it “Relies, at local and referral levels, on health workers, including physicians, nurses, midwives, auxiliaries and community workers as applicable, as well as traditional practitioners as needed, suitably trained socially and technically to work as a health team and to respond to the expressed health needs of the community”.